f f e c t of phosphorus and farmyard manure application on yield, content and uptake of nitrogen, phosphorus and sulphur by potato (Solanum tuberosum) - SHASHI PAL SINGH; VINAY SINGH; RhM LAKHAN (Indian Journal of Agronomy, 2001)
In a field experiment conducted during 1990-92 on light-textured soil, the efficiency of farmyard manure (FYM) and phosphatic fertilizer (alone and in combination) was evaluated for potato [Solanum tuberosum L.). Application of P and FYM individually or in combination increased significantly the tuber yield of potato. The concentration of N, P and S in tubers increased with FYM but S content was not affected by applied P. Addition of P and FYM significantly enhanced the uptake of N, P and S by potato tubers.